BAURAN PEMASARAN PRODUKSI SALAK TERHADAP PENINGKATAN PEROKONOMIA MASYARAKAT DI BOJONEGORO (STUDI KASUS PETANI SALAK TANJUNGHARJO) - Mukti Prasaja (Sekolah Tinggi Ilmu Ekonomi Cendekia Bojonegoro, 2019)
Bojonegoro is one of regencies in East Java province that has many natural and cultural richness. Natural riches range from fertile farmland, petroleum and gas, limestone mountains, eternal fires and much more. In agriculture there are rice crops, corn, nuts and others. Meanwhile, for the results of the garden are blimbing, Salak, banana, mango and guava. However, there are problems, namely the marketing of these products are still difficulties in branding, packaging and also promoting the products globally. The marketing mix approach focuses on the resulting product must be good and attractive so as to provide satisfaction to the consumer. High consumer satisfaction will build a good relationship with the producers so that it will improve the economy. Implementation of the marketing mix is done in the training of ice cream production, mapping and branding of products and the establishment of KUB Desa Tanjungharjo, product Expo, marketing training which to advance the community economy Bojonegoro. Keyword :